2003
DOI: 10.1113/jphysiol.2003.051862
|View full text |Cite
|
Sign up to set email alerts
|

Mechanotransduction by intraganglionic laminar endings of vagal tension receptors in the guinea‐pig oesophagus

Abstract: Vagal mechanoreceptors to the guinea-pig oesophagus, recorded extracellularly, in vitro, fired spontaneously at 3.3 ± 0.2 Hz, (n = 75, from 57 animals), and had low thresholds to circumferential stretch. In this study, we have investigated whether mechanotransduction by intraganglionic laminar endings (IGLEs) directly relies on mechano-gated ion channels, or whether it is due to chemical activation by neurotransmitters (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
143
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(162 citation statements)
references
References 66 publications
(83 reference statements)
16
143
3
Order By: Relevance
“…Although mechanosensitive structures have not been described in the small or large intestine, circumferential stretch of the esophagus, stomach, and rectum is thought to be detected by intraganglionic laminar endings (IGLEs) (Lynn et al, 2003;Zagorodnyuk and Brooks, 2000;Zagorodnyuk et al, 2001). Indeed, Zagorodnyuk et al (2003) recently reported that esophageal IGLEs directly transduce mechanical stimuli. The identity of the molecules that confer mechanosensitivity to these structures is unknown, but we provide evidence to suggest that TRPV1 and ASIC3 may contribute to this function.…”
Section: Discussionmentioning
confidence: 99%
“…Although mechanosensitive structures have not been described in the small or large intestine, circumferential stretch of the esophagus, stomach, and rectum is thought to be detected by intraganglionic laminar endings (IGLEs) (Lynn et al, 2003;Zagorodnyuk and Brooks, 2000;Zagorodnyuk et al, 2001). Indeed, Zagorodnyuk et al (2003) recently reported that esophageal IGLEs directly transduce mechanical stimuli. The identity of the molecules that confer mechanosensitivity to these structures is unknown, but we provide evidence to suggest that TRPV1 and ASIC3 may contribute to this function.…”
Section: Discussionmentioning
confidence: 99%
“…IGLEs are the mechanotransduction sites of vagal tension receptors (Zagorodnyuk and Brookes, 2000;Zagorodnyuk et al, 2003), the nNOS inhibitor did not affect their mechanosensitivity. Therefore, the NO produced by myenteric neurons does not reach IGLEs surrounding them at sufficient concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…By comparing dye-filled nerve endings with carbon marks on the tissue, the sensory endings of low-threshold vagal mechanoreceptors were shown to correspond to intraganglionic laminar endings (IGLEs) located in myenteric ganglia. 24,25 These IGLEs detect distortion of the surrounding tissue by as-yet-unidentified stretchactivated ion channels 26 and probably signal gastric distension after a meal. They end inparallel with the smooth muscle fibres of the gut wall, yet respond mechanically as in-series tension receptors.…”
Section: Vagal Intraganglionic Laminar Mechanoreceptorsmentioning
confidence: 99%
“…32 An intriguing feature of IGLEs, shared by many other visceral afferents, is their sensitivity to a range of biological mediators. IGLEs are potently excited by ATP, 26,33 probably when this biochemical is released from damaged cells 34 ATP might also couple mechanosensitive epi-thelia to excitation of mechanoreceptors; 35,36 however, the time course of ATP release and its effects preclude a role in mechanotransduction by IGLEs. 26 The same endings in ferret stomach and oesophagus express inhibitory GABA B receptors, 37 excitatory and inhibitory metabotropic glutamate receptors 38,39 and are inhibited by ghrelin.…”
Section: Vagal Intraganglionic Laminar Mechanoreceptorsmentioning
confidence: 99%